Critical airway obstruction in apparently asymptomatic neonates. Issue 4 (18th September 2016) - Griffiths, Benedict; Lee, Geraint; Durward, Andrew
Summary: Central airway obstruction (trachea and major bronchi) in neonates can be caused by malacia, stenosis, or compression by masses or vascular structures. These abnormalities may be present in the neonatal period but are typically not detected until at least 6 months of age. We present four patients (1.6–4.1 kg, 32–41 weeks gestation) with nonspecific symptoms (e.g., poor weight gain, difficulty weaning from CPAP) who underwent bronchoscopy in the neonatal period. Critical airway obstruction (>90%) was identified in these relatively asymptomatic neonates. We suggest a low threshold for investigation with bronchoscopy in high‐risk neonates. Pediatr Pulmonol. 2017;52:E15–E17. © 2016 Wiley Periodicals, Inc.